Cognitive stimulation in older adults: an innovative good practice supporting successful aging and self-care - Apóstolo, J. (2019)
The project Cognitive Stimulation in Older Adults: Intervention on Cognitive Frailty and Promotion of Self-Care (in brief the ECOG project) arises in a context of worldwide demographic aging, and is fostered by the need to provide a sustainable solution to the progressive increase in the prevalence of age-related cognitive impairment. The main goal of the ECOG project is to promote active citizenship in old age through the empowerment for autonomy and self-care. Namely, the ECOG team is working on the development of evidence-based programs and tools that promote gains in health in cognitively frail and cognitively impaired older adults from the community. It is also working on the transfer of ECOG products to the practice of health and social care, promoting active involvement of geriatric care institutions in the implementation of the ECOG programs and tools, and ensuring appropriate training of professionals. Finally, the ECOG team is deploying a digital platform to reach out to the broadest audience possible and support the remote access and scaling up of the ECOG products. The impacts expected at an individual level include improvements in cognition, functionality, and autonomy of older adults, with simultaneous reduction of depressive symptomatology, and increase in quality of life of both person cared and his/her caregiver. Regarding societal gains, we anticipate an increase in life expectancy and significant postponement of institutionalization associated with geriatric problems. We also believe that the wide implementation of the ECOG products will reduce the costs of interventions for cognitively impaired citizens, contributing to sustainability and efficiency of health systems.